Pengaruh Peer education Breast Self Examination Terhadap Perilaku Remaja Dalam Deteksi Dini Kanker Payudara - Sitindaon, Sry Rumondang; Nasution, Siti Zahara (Universitas Muhammadiyah Semarang, 2024)
Adolescents have less attitude towards breast cancer, making prevention and treatment very difficult. The more conscious about one's health the more understanding the importance of disease prevention, especially the risk of breast cancer. The main cause of breast cancer has not been ascertained, only one of them is hormonal, hereditary factors and congenital mutations in genes such as BRCA1 and BRCA2, which are predisposing factors to breast cancer. The main cause of breast cancer has not been ascertained, only one of them is hormonal, hereditary factors and congenital mutations in genes such as BRCA1 and BRCA2, which are predisposing factors to breast cancer. Gene expression mutations account for about 5-10% of all breast cancer cases. This literature review aims to analyze the effect of Peer Education breast self-examination on adolescent behavior in breast cancer detection. The search began by finding hundreds of references in the Google Scholar and Science Direct databases, published between 2018-2023 with the database Breast Self Examination, Impact of Peer Education on Nursing Delivery. Of the 150 articles, 10 articles met the inclusion criteria, namely: published between 2018-2023; Internationally recognized journals (DOI, ISBN, ISSN) the exclusion criteria set out in this method are: journals published outside 2018-2023; journals without international recognition (DOI, ISBN, ISSN). Ten literature reviews related to the impact of peer Education Breast Self Examination on adolescent behavior in early detection of breast cancer were screened based on the results of literature review. The results of the ten literatures had a significant influence before and after education and intervention on Breast Self Examination